Optimal Dispatch of Distribution Network with Integrated Photovoltaic Storage Power Station Considering Harmonic Control - ZHONG Hao, ZHANG Yonghao, ZOU Xianqiu, WANG Qiujie, LIU Haoyu, WANG Xinghuo (Dianli jianshe, 2025)
[Objective] The flexibility of the power control of grid-connected inverters in integrated photovoltaic storage power stations makes them a good resource for participating in distribution network harmonic control. [Methods] This study proposes a two-layer optimization model for a distribution network with an integrated photovoltaic storage power station considering harmonic control. The upper layer establishes the optimization model of the distribution network and integrated photovoltaic storage power station. The distribution network sets the harmonic compensation price to maximize revenue， thus guiding the integrated photovoltaic storage power station to optimize the multi-functional grid-connected inverter active grid-connected and harmonic control capacity. The lower layer establishes the optimization model of the distribution network and the demand user and the demand user according to the electricity price and the cost of electricity use of different harmonic control levels before developing a power pur